The Effect of Good Corporate Governance on Tax Avoidance: Empirical Study on Trade, Service and Investment Company Listed on the Indonesia Stock Exchange Period of 2016 - 2020 - Mar'atul 'Ainish Sholikhah; Fajar Nurdin (Politeknik Keuangan Negara STAN, 2022)
This research objectives to find out the effect of independent commissioners, institutional ownership, managerial ownership, and audit committees on tax avoidance of service companies listed on the IDX in 2016-2020. This study is a quantitative type using multiple linear regression analysis as a hypothesis test. This study used secondary data from the financial statements of service companies listed on the IDX in 2016-2020. There are 28 samples of service companies listed on the IDX with a research period of 2016-2020 which were selected using the purposive sampling method used in this research. The results showed that the independent board of commissioners, institutional ownership, managerial ownership, and the audit committee had a significant positive effect on tax avoidance with a coefficient of determination of 40.1%. Thus, it can be said that independent commissioners, institutional ownership, managerial ownership, and audit committees have an important role in tax planning, namely tax avoidance. Penelitian ini untuk mengetahui pengaruh dewan komisaris independen, kepemilikan institusional, kepemilikan manajerial dan komite audit terhadap tax avoidance dari perusahaan jasa yang terdaftar di BEI tahun 2014–2020. Penelitian ini berjeniskuantitatif dengan menggunakan menggunakan analisis regresi linear berganda sebagai uji hipotesis . Penelitian ini menggunakan data sekunder dari laporan keuangan perusahaan jasa yang terdaftar di BEI periode 2014 - 2020. Terdapat 28 sampel perusahaan jasa yang terdaftar di BEI dengan periode penelitian tahun 2014 – 2020 yang dipilih menggunakan metode purposive sampling yang digunakan di dalam penelitian ini. Hasil penelitian menunjukkan bahwa dewan komisaris independen, kepemilikan institusional, kepemilikan manajerial dan komite audit berpengaruh positif signifikan terhadap tax avoidance dengannilai koefisien determinasi sebesar 34,1%. Sehingga dapat dikatakan dewan komisaris independen, kepemilikan institusional, kepemilikan manajerial dan komite audit memilikiperan penting di dalam melakukan perencanaan pajak yaitu tax avoidance.